(untitled) (Minerva, 2018)
At the end of the first book of the Anonymous Commentary to Ptolemy’s Tetrabiblos (Anon. in Ptol.), a few manuscripts contain a text entitled On the signs indicating amorous desires. The first paragraph of this text is chapter 27 of the Greek translation (ca. 1000 AD) from the Great Book of the Introduction to Astrology by Abū Ma‘shar (787-886; in latin, Apomasar). But establishing the authorship of the remaining paragraphs (2-7) is much more problematic, because no trace of them has been found in Abū Ma‘shar’s edited works. Since a definitive confirmation will not be possible until the whole corpus of the Persian astrologer has been edited, the main goal of this paper is to publish the first critical edition of the text, as well as a comparative analysis of its technical terms and astrological doctrines, on the one hand, and the main features of other parallel passages found in Byzantine translations from works of Abū Ma‘shar, on the other.